Spatial distribution of annelids in the intertidal zone in Sao Sebastiao Channel, Brazil - Alexandra E. Rizzo (Scientia Marina, 2001)
We studied the spatial distribution of annelids in the intertidal zone of two beaches (Engenho d´Água and São Francisco) in São Sebastião Channel, southeastern Brazil, from August 1995 through July 1996. This region is commonly affected by oil spills and sewage waste. The substratum of the two beaches is composed of a mixture of sand and rock fragments. We established three levels (100 m2) in the intertidal zone of each study site: lower, intermediate, and upper. In general, species richness increased from upper towards lower levels. The distribution of species at Engenho d´Água was more homogeneous than at São Francisco. Only some individual spatial patterns were recognised at São Francisco. The most abundant polychaete species at Engenho d´Água (Nematonereis hebes, Timarete filigera, and Scyphoproctus djiboutiensis) occurred in the intermediate and lower levels. The upper level of São Francisco was characterised by a peak of opportunists, with a large number of individuals but few dominant species (Capitella sp., Scolelepis squamata, Laeonereis acuta, and the oligochaete Tubifex sp).